Financial Distress and Accounting Conservatism On Tax Avoidance - Wulandari, Dian Sulistyorini; Purba, Jamian; Wijayanti, Ruri (Akuisisi : Jurnal Akuntansi, 2024)
Tax avoidance can be interpreted as an effort to avoid taxes that is carried out legally and safely for taxpayers because it does not conflict with applicable tax laws. This study aims to test and analyze the effect of financial distress and accounting conservatism on tax avoidance. The population used in this study were all property, real estate, and building construction companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021, with a population of 83 companies. The sampling method in this study was purposive sampling. The sample used was 14 companies, with an observation period of 4 years. The data analysis method used multiple linear regression analysis using Statistical Product and Service Solution (SPSS) software version 23. The results of this study indicate that financial distress and accounting conservatism simultaneously affect tax avoidance. [Based on the results of the partial test (t-test), financial distress has a negative effect on tax avoidance while accounting conservatism has no effect on tax avoidance.